Distinct functional roles of the mirror neuron system and the mentalizing system - Geiger, Alexander; Bente, Gary; Lammer, Sebastian; Tepest, Ralf; Roth, Daniel; Bzdok, Danilo; Vogeley, Kai (NeuroImage, 2019)
Movements can inform us about what people are doing and also about how they feel. This phenomenologically evident distinction has been suggested to correspond functionally with differential neural correlates denoted as mirror neuron system (MNS) and mentalizing system (MENT). To separate out the roles of the underlying systems we presented identical stimuli under different task demands: character animations showing everyday activities (mopping, sweeping) performed in different moods (angry, happy). Thirty-two participants were undergoing functional magnetic resonance imaging (fMRI) while asked to identify either the performed movement or the displayed mood. Univariate GLM analysis revealed the expected activation of either in MNS or MENT depending on the task. A complementary multivariate pattern-learning analysis based on the “social brain atlas” confirmed the expected recruitment of both systems. In conclusion, both approaches converge onto clearly distinct functional roles of both social neural networks in a novel dynamic social perception paradigm.
CRIS-Team Scopus Importer:2021-03-29
Keywords: Functional magnetic resonance imaging (fMRI); Machine learning; Mentalizing system; Mirror neuron system; Whole body movement